The Perfective, the Progressive and the (dis)closure of situations: comment on the paper by María J. Arche - Pratas, Fernanda (2018)
In the present paper, inspired by María J. Arche’s work, “The construction of viewpoint aspect: the imperfective revisited” (2013, this issue), I add several pieces of evidence in favor of her proposal that viewpoint aspect does not alter the fundamental situation aspect properties of predicates. Namely, I discuss the temporal interpretations in Capeverdean, a Portuguese-based Creole language for which the salient opposition in the domain of viewpoint aspect is not between the imperfective and the perfective, but rather between the Progressive and the Perfect, here taken as semantically complex categories that involve certain temporal characteristics; crucially, imperfectivity is one of the features of the Progressive and a perfective viewpoint is part of the semantic complexity of the Perfect. I also discuss the role of for-time durational adverbials when combined with the perfective and propose that, in their presence, the relevant final boundary when telic predicates are at stake is not the culmination of the event, but rather the final point described by that time-argument. This proposal accounts nicely for the fact that, in these specific contexts, there is no contradiction in having this perfective clause conjoined with the assertion that the underlying telic situation is not completed.